NEUROPATI PERIFER PADA PASIEN KARSINONMA NASOFARING YANG MENDAPAT KEMOTERAPI CISPLATIN - Winnugroho Wiratman, Manfaluthy Hakim, Tiara Aninditha, Aru W. Sudoyo, Joedo Prihartono (Neurona Majalah Kedokteran Neuro Sains, 2013)
INTRODUCTION THE MAJORITY OF CANCER PATIENTS WILL EXPERIENCE NEUROPATHY NEUROPATHIC SYMPTOMS ARISING FROM CHEMOTHERAPY CAN INHIBIT THE THERAPEUTIC PROCESS CISPLATIN IS THE MOST WIDELY USED CHEMOTHERAPY IN THE OF NASOPHARYNGEAL CANCER NPC TREATMENT AND CAN CAUSE PERIPHERAL NEUROPATHY